FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KELELAHAN MATA PADA PEKERJA HOME INDUSTRY BATIK TULIS LASEM - Tri Utami, Annisa Rachmah; Suwondo, Ari; Jayanti, Siswi (Jurnal Kesehatan Masyarakat (Undip), 2018)
Eye strain or asthenopia is eye function disorder caused by intensive and prolonged use of near vision when working which requires precision. The purpose of this research was to analyze the risk factors related to eye strain among batik Lasem workers. The type of this research was descriptive analytic research with cross sectional study approach. The population and sample consisted of 26 workers. Based on analysis showed that 76,9% of workers experienced eye strain after working while Chi Square and Odd Ratio test showed that age was the risk factor of eye strain (p value=0,013; OR=18,000; CI=1,917-168,991), eye refraction was the risk factor of eye strain (p value=0,028; OR=19,000; CI=1,454-248,237), the eye distance to work object was the risk factor of eye strain (p value=0,018; OR=15,000; CI=1,397-161,045) and local light intensity was the risk factor of eye strain (p value=0,028; OR=19,000; CI=1,454-248,237). Suggestion for the home industry owner is to fix the lay out of work station while for workers are recommended to do eye rest and use corrected refraction eye glasses for those who have eye refraction abnormality.